Kualitas Pelayanan di Puskesmas Boja 1 - Sekawanie, Denayu; Rahma, Lutfiana Nur; Desty, Rani Tiara (Universitas Ivet, 2023)
The concept of quality (quality) has become a reality and phenomenon in all aspects and dynamics of global society entering today's free market competition. The quality or quality of health services cannot be separated from customer or patient satisfaction. Quality health services can increase patient satisfaction with the services provided. In addition, patient satisfaction can be used as a measure of the success of the quality of service in a health facility. Based on the preliminary study, there were complaints that were obtained from the suggestion box, in person or online about the quality of service at the Boja 1 Health Center, such as inadequate facilities and unfriendly health center staff. The purpose of this study was to determine the quality of service at the Boja 1 Health Center. This study used a descriptive observational study with a cross-sectional design. The method used was purposive sampling by determining respondents who had conducted an examination at the Boja 1 Health Center. The results showed that almost all respondents considered the quality/quality of the Boja 1 Health Center to be good enough, while half of the respondents considered that the performance of officers based on efficiency in providing services was not good. . It is necessary to improve the quality of performance by optimizing services so as to improve the quality standards of the Boja Health Center more efficiently.